Paradoxical Vitamin D deficiency in a sunny country: A narrative review of the literature from the United Arab Emirates (1992–2018) - Beshyah, Salem; Hafidh, Khadija; Abdelmannan, Dima; Jabbar, Abdul; Wafa, Wafic; Khalil, Aly (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Deficiency of Vitamin D is a global problem related to lack of sunlight exposure and reduced dietary intake. Vitamin D deficiency (VDD) affects mainly skeletal structure and function but has a number of recognized nonskeletal effects that have wide ramifications. It sounds ironic that low serum Vitamin D levels are widely documented in a sunny country like the United Arab Emirates (UAE). The study objective was to review the literature on VDD in the UAE. This is a narrative nonsystematic review of the literature on the epidemiological and clinical aspects of Vitamin D status in the UAE based on PubMed search using two search terms “Vitamin D” and “Emirates.” We discuss the various themes that emerged as follows: epidemiology and disease burden of VDD in the UAE population in general and in specific groups (adults, children, females, and pregnant and nursing mothers); awareness of dietary intake, climate, genetics, and metabolic factors affecting serum Vitamin D levels; and the overview of current clinical management guidelines, interventional trials, and clinical practices. VDD is a widely documented health problem in the UAE population as a whole and in several special groups. This may have serious skeletal and nonskeletal health implications.
Keywords: Adult population; diet; direct sun exposure; epidemiology; female health; genetic polymorphism; joint and bone weakness; Middle East; obesity; sunlight; United Arab Emirates; Vitamin D deficiency